Decolonizing Knowledges: Asian American Studies, Carlos Bulosan, and Insurgent Filipino Diasporic Imagination - Cabusao, Jeffrey Arellano (Archīum Ateneo, 2024)
The current wars in Iraq and Afghanistan have compelled interdisciplinary scholars to seek new methods of engaging US Empire. This essay will attempt to outline an emerging critique-al strand of Filipino Cultural Studies that challenges the limitations of the “cultural turn” through its connection to the larger goal of creating movements for social justice. Over the past few years, new forms of Filipino American scholarship have advanced a unique tradition of class analysis developed by earlier generations of Filipino cultural workers and activists. In addition to this new development, Filipino American cultural workers have created politically conscious art through their participation in social justice movements. I argue that this new form of Filipino Cultural Studies – one that is not strictly ensconced in the academy – might provide useful and timely suggestions for alternative and transformative ways of knowing and being.